2017
DOI: 10.1136/bmjopen-2016-015615
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a postnatal metabolic gestational age algorithm: a retrospective validation study among ethnic subgroups in Canada

Abstract: ObjectivesBiological modelling of routinely collected newborn screening data has emerged as a novel method for deriving postnatal gestational age estimates. Validation of published models has previously been limited to cohorts largely consisting of infants of white Caucasian ethnicity. In this study, we sought to determine the validity of a published gestational age estimation algorithm among recent immigrants to Canada, where maternal landed immigrant status was used as a surrogate measure of infant ethnicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…In this way, we sought to determine whether one global algorithm would be adequate for estimating GA across ethnic subgroups, or whether local model calibration would likely be required in each new setting. Our results indicated that tailored algorithms may help to improve the precision of GA estimation, but our model performed well among infants from a variety of ethnic backgrounds [24], although there was some variation in accuracy of GA estimation. Among non-immigrant mothers, the model estimated GA to within an average of 1.05 weeks of true GA, while among immigrant mothers, estimates ranged from 0.98 to 1.15 weeks of true GA [24].…”
Section: Model Refinement and Ethnic Validationmentioning
confidence: 81%
See 1 more Smart Citation
“…In this way, we sought to determine whether one global algorithm would be adequate for estimating GA across ethnic subgroups, or whether local model calibration would likely be required in each new setting. Our results indicated that tailored algorithms may help to improve the precision of GA estimation, but our model performed well among infants from a variety of ethnic backgrounds [24], although there was some variation in accuracy of GA estimation. Among non-immigrant mothers, the model estimated GA to within an average of 1.05 weeks of true GA, while among immigrant mothers, estimates ranged from 0.98 to 1.15 weeks of true GA [24].…”
Section: Model Refinement and Ethnic Validationmentioning
confidence: 81%
“…Our results indicated that tailored algorithms may help to improve the precision of GA estimation, but our model performed well among infants from a variety of ethnic backgrounds [24], although there was some variation in accuracy of GA estimation. Among non-immigrant mothers, the model estimated GA to within an average of 1.05 weeks of true GA, while among immigrant mothers, estimates ranged from 0.98 to 1.15 weeks of true GA [24]. This suggested that our global model could perform well across a wide variety of settings but might be further improved through local calibration in new settings.…”
Section: Model Refinement and Ethnic Validationmentioning
confidence: 81%
“…Unique to this study is our evaluation of the impact of alterations in metabolic profiles over time on the performance of gestational age estimation models developed by our group. We have previously demonstrated the accuracy of such algorithms to estimate gestational age to within one week when applied to infants born in Ontario, Canada 3 7 9 . Gestational age algorithms such as those described here have the potential to provide reliable population-level estimates of preterm birth for jurisdictions where such data are currently lacking 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Validation of metabolic gestational age estimation models. Our group has previously developed and validated gestational age estimation algorithms derived from newborn screening profiles and other clinical covariates 3 7 9 . Linear regression models were developed to estimate continuous gestational age, and logistic models were fit to classify infants as term (≥ 37 completed gestational age weeks) or preterm (<37 completed gestational age weeks).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation